Discourse on Social Problems in Society and Gender Equality Stereotypes in the Media - Kostiuk, Shirin; Duishekeeva, Aina; Taabaldiev, Kubanychbek; Aldashova, Gulanda; Esenkelova, Elnura (Italian Sociological Review, 2026)
This study aims to comprehensively examine the issue of gender equality in Kyrgyzstan. To achieve this goal, relevant statistical data was analysed and a monitoring of the country’s most popular mass media outlets was conducted. As a result of the study, a positive dynamic in the gender balance was revealed, with the gap between the number of men and women decreasing by 3.5% over 50 years. The effectiveness of introducing gender quotas for political parties running for the Jogorku Kenesh and local keneshes into the Kyrgyz political system was also investigated. A comparison was made between the representation of women in legislative bodies of the Republic before and after the adoption of the relevant Law. A separate analysis was conducted of the ratio of men and women holding public office positions, as well as their salary levels. The study of the results from the nationwide testing revealed a contradiction where girls, who achieved a higher average score, tended to abandon their careers and become homemakers after completing their studies. Additionally, a monitoring of television channels such as the National Broadcasting Corporation of the Kyrgyz Republic (KTRK), Ala-Too 24, and the most popular social media platforms revealed a promotion of negative gender stereotypes. The research identified and demonstrated, through examples, the existing gender issues within Kyrgyz society, and also highlighted the correlation between an increase in the number of female professionals and the strengthening of the country’s economy.